The historic verdict of ITLOS on maritime border delimitation in the region of the Bay of Bengal: A historical analysis - Hossain, Md Shayeed; Ullah, Md Cholem; Absar, ABM Nurul (IIUC Studies, 2022)
In 1982, the United Nations Convention on the Law of the Sea (UNCLOS) established the International Tribunal for the Law of the Sea (ITLOS) as an independent tribunal to sit in judgment on resolving maritime clash between the states. The ITLOS published on 14 March 2012 its case judgment on the Dispute Maritime Border between Bangladesh and Myanmar in the sea area of the Bay of Bengal. That tribunal was asked to demarcate three maritime borders; the Territorial Sea Border, Exclusive Economic Zone (EEZ), and Continental Shelf beyond EEZ were the principles of delimitation. The article focuses on analyzing and investigating the main features of the remarkable verdict from the historical perspectives. This paper also attempts to study its significant implication in sharing sea resources from both countries. Regional relations and border security tension can be more exposed in the regional geopolitics due to the judgment. Therefore, Bangladesh will adopt effective roles in the chessboard of south Asian regional politics following significant historical lessons of past and present. IIUC Studies Vol.18, December 2021: 173-192